Management of Skin Disorders in Ayurveda : A Review - Shah, Sonal; chingale, Amit; Gambhire, Varashali (International Research Journal of Ayurveda & Yoga, 2022)
Skin is the largest organ of human body. Its size and external location makes it susceptible to various disorders. Skin diseases are mostly caused by infections like bacteria, fungi etc. All the skin diseases in Ayurveda have been classified under the broad heading of Kushta which are further classified into Mahakushta and Kshudrakushta. Ayurveda has its own unique principles of diagnosis and treatment of various skin diseases under the heading of Kuṣṭha. A review was conducted from the relevant texts of Ayurvedic and contemporary science to collect information about the skin diseases and their treatment through Ayurveda. The review concluded that Ayurveda management through Shodhana and Shamana Chikitsa (with Ayurvedic herbs) is beneficial in skin diseases.